Microtubule behavior in the growth cones of living neurons during axon elongation (The Rockefeller University Press, 1991)
To understand how microtubules are generated in the growth cone, we have imaged fluorescently tagged microtubules in living frog embryonic neurons. The neurons were labeled by injecting rhodamine-labeled tubulin into the fertilized egg and explanting the neurons from the neural tube. Microtubules extend deep into the growth cone periphery and adopt three characteristic distributions: (a) dispersed and splayed throughout much of the growth cone; (b) looped and apparently contorted by compression; and (c) bundled into tight arrays. These distributions interconvert on a time scale of several minutes and these interconversions are correlated with the behavior of the growth cone. We observed microtubule growth and shrinkage in growth cones, but are unable to determine their contribution to net assembly. However, translocation of polymer form the axon appears to be a major mechanism of generating new polymer in the growth cone, while bundling of microtubules in the growth cone appears to be the critical step in generating new axon. Neurons that were about to turn spontaneously generated microtubules in the future direction of growth, suggesting that orientation of microtubules might be an important early step in neuronal pathfinding.